UKT PAYMENT CONTRIBUTION TO THE EXISTENCE OF SHARIA BANKING - Ferlita Natania; Sri Rahayu; Dela Setiawati; Ulfa Dhea Nova; Dila Puspita Sari; Ahmad Ridho; Hepi Agustini; Berliana; Pangestu (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2023)
Payment of UKT (Single Tuition Fee) by students at tertiary institutions in Indonesia has an important contribution to the existence and development of Islamic banking. UKT payments play a role in increasing the number of Islamic bank customers in Indonesia. UKT paid by students often involves the banking system to manage and distribute these funds. Many universities in Indonesia have collaborated with sharia banks to provide UKT payment facilities that comply with sharia principles. Through the involvement of Islamic banks in the UKT payment process, students tend to be more inclined to use Islamic banking products and services. Thus, UKT payments contribute to an increase in the number of Islamic bank customers in Indonesia. the use of funds from UKT payments can help the development of the Islamic economy in Indonesia. Funds collected from UKT payments can be used by Islamic banks to support Islamic economic activities, such as financing micro, small and medium enterprises (UMKM) in accordance with sharia principles. Through the utilization of these funds, Islamic banks can provide financial access to sharia-based business actors, thereby strengthening the Islamic economic sector in Indonesia. In addition, funds from UKT payments can also be used for sharia banking product development and innovation, increasing operational efficiency, and expanding the range of services.